HEAVY METAL LEVELS IN MEAT OF SPINY DOGFISH (SQUALUS ACANTHIAS) FROM BULGARIAN BLACK SEA - Veselin Kirov; Neshovska, Hristina; Manev, Iliyan (Zenodo, 2022)
Environmental pollution with heavy metals and other toxic elements can serve as a predisposing factor for a various type of human diseases. Their accumulation in aquatic organisms used for human consumption increases the risk for daily intake of low doses of heavy metals. The Black Sea spiny dog (Squalus acanthias, Linnaeus 1758) is a cartilaginous fish predator belonging to the spiny shark family. This demersal fish belongs to the common monitoring species in Bulgaria and Romania in terms of pollution of the Black Sea. In this regard, the aim of the present study was to determine the concentrations of As, Pb, Cd, Hg, Mn, Zn and Al in shark meat samples, caught from our northern Black Sea coast (Varna region). The element with the highest concentration was arsenic. Mercury levels have been found to be above the permissible levels set out in Euro-pean and national legislation, which poses a potential health hazard risk for the consumers. : {"references": ["Arnaudova D, Arnaudov A. and Sapundzhiev E. (2011). Metabolic Glycogen Activity in Hepatocytes of Fish from a Water Source Containing Heavy Metals. Acta morphologica et anthropologica, 17 Sofia, 2011, ISSN 0861-0509", "Bat L., Arici E., Sezgin M., Sahin F. (2017). Heavy Metal Levels in Commercial Fishes Caught in the Southern Black Sea Coast. International Journal of Environment and Geoinformatics 4(2). 94\u2013102. 10.30897/ijegeo.312584", "Bat L., Sahin F., Ustun F., Sezgin M. (2012). Distribution of Zn, Cu, Pb and Cd in the Tissues and Organs of Psetta Maxima from Sinop Coasts of the Black Sea, Turkey. Marine Science, 2(5): 105\u2013109. 10.5923/j.ms.20120205.10", "Commission Regulation (EC) No 1881/2006 of 19 December 2006 setting maximum levels for cer-tain contaminants in food stuffs. Official Journal of the European Union, L 364/5, 20.12.2006", "Daskalov G. (1998). Using abundance indices and fishing effort data to tune catch -at-age analyses of sprat Sprattus sprattus L., whiting Merlangius merlangus L. and spiny dogfish Squalus acanthias L. in the Black Sea. In: Lleon art J. (ed.). Dynamique des populations marines. Zaragoza: CIHEAM, p. 215\u2013228", "Domi N., Bouquegneau J.M., Das K. (2005). Feeding ecology of five commercial shark species of the Celtic Sea through stable isotope and trace metal analysis. Marine Environmental Research, Volume 60, Issue 5, 2005, p. 551\u2013569, https://doi.org/10.1016/j.marenvres.2005.03.001.", "Endo T., Hisamichi Y., Kimura O., Kotaki Y., Kato Y., Ohta C., Koga N., Haraguchi K. (2009). Contamination levels of mercury in the muscle of female and male spiny dogfishes (Squalus acan-thias) caught off the coast of Japan. Chemosphere. 2009 Nov; 77(10):1333\u20137. doi: 10.1016/j.chem-osphere.2009.09.041. Epub, Oct 27. PMID: 19863992", "Fazio F., D'Iglio C., Capillo G., Saoca C., Ivanova K., Piccione G., Makedonski L. (2020). Environ-mental Investigations and Tissue Bioaccumulation of Heavy Metals in Grey Mullet from the Black Sea (Bulgaria) and the Ionian Sea (Italy). Animals: an open access journal from MDPI. 10. 10.3390/ani10101739.", "Kumari B., Kumar V., Sinha A., Ahsan J., Ghosh A. Wang H., De Boeck G. (2016). Toxicology of arsenic in fish and aquatic systems. Environmental Chemistry Letters. 14. 1\u201322. 10.1007/s10311-016-0588-9.", "Medeiros R., dos Santos L., Freire A., Santelli R. E., Braga A. M., T.M., Jacob S. (2012). Determi-nation of inorganic trace elements in edible marine fish from Rio de Janeiro State. Brazil, Food Control, Volume 23, Issue 2, 2012, p. 535\u2013541, https://doi.org/10.1016/j.foodcont.2011.08.027", "Nisbet C., Terzi G., Pilger O., Sarac N. (2010). Determination of heavy metal levels in fish sample collected from the Middle Black Sea. Kafkas \u00dcniv.Veteriner Fak. Dergisi, 16(1): 119\u2013125.", "Stancheva M., Makedonski L., Ivanova K. (2014). Determination of heavy metal concentrations of most consumed fish species from Bulgarian Black Sea coast. Bulgarian Chemical Communications. 46. 195\u2013203", "Stancheva M., Makedonski L., Petrova-Pavlova E. 2013. Determination of heavy metals (Pb, Cd, As and Hg) in Black Sea grey mullet (Mugil cephalus). Bulgarian Journal of Agricultural Science. 19. 30\u201334.", "Tuzen M. (2009). Toxic and essential trace elemental contents in fish species from the Black Sea, Turkey. Elsevier Publishing, Food and Chemical Toxicology. vol.47, No.8, 1785\u20131790"]}